Candida albicans overgrowth disrupts the gut microbiota in mice bearing oral cancer - Wang, Xu; Wu, Shuangshaung; Li, Linman; Yan, Zhimin (Mycology, 2024)
Candida albicans is one of the most common opportunistic fungi in cancer patients. This study explored the influence of C. albicans on gut microbiota in oral tumour-bearing mice by means of 16S rRNA sequencing and ITS sequencing. It was found that C. albicans infection induced the decrease of alpha diversity of bacteria and fungi in the gut microbiome. For the bacteria, C. albicans caused the reduction of Ralstonia, Alistipes, Clostridia UCG-014, Ruminococcus, and Lachnospiraceae NK4A136 group. For the fungi, C. albicans inhibited the growth of other fungi including Aspergillus, Cladosporium, and Bipolaris. The neutralisation of γδT cells partly alleviated the out-of-balance of Firmicutes/Bacteroidota (F/B) ratio in the gut caused by C. albicans infection. However, γδT cell neutralisation boosted the overgrowth of C. albicans. Additionally, IL-17A neutralisation aggravated the microbial dysbiosis of bacteria and fungi caused by C. albicans infection. Further analysis indicated that C. albicans overgrowth might influence the correlations between fungal and bacterial kingdoms. In conclusion, C. albicans infection disturbed the gut microbiota of both bacteria and fungi in oral tumour-bearing mice, which may be associated with the intestinal immune components including γδT cells and IL-17A.